2005
DOI: 10.1111/j.1365-2044.2004.04086.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric investigation of peri‐anaesthetic anaphylaxis using CD63 and CD203c

Abstract: SummaryThe investigation of anaphylactic reactions in the peri-operative period is difficult. Elevation of serum tryptase levels is a good indicator of an anaphylactic event but the ability of subsequent investigations to identify the drug(s) responsible for the reaction is still potentially unreliable. The aim of this study was to examine basophil activation as an investigative tool. We performed flow cytometric analysis of the expression on the cell surface of the basophil activation markers CD63 and CD203c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
1
11

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(87 citation statements)
references
References 11 publications
2
73
1
11
Order By: Relevance
“…Most of these studies reported a high specificity and a sensitivity above 50%, reaching 91% (Abuaf et al, 1999;Kvedariene et al, 2006;Laxenaire et al, 1999;Monneret et al, 2002;Moss, 1995;Stellato et al, 1991). This sensitivity is lower (36%) when the marker CD203c is used (Sudheer et al, 2005). However, results are discordant; Kvedarine et al (Kvedariene et al, 2006) observed in 47 patients a sensitivity of 36% and a specificity of 93% performing BAT (CD63 in whole blood).…”
Section: Basophil Activation Test In Muscle Relaxant Allergic Reactionsmentioning
confidence: 62%
See 1 more Smart Citation
“…Most of these studies reported a high specificity and a sensitivity above 50%, reaching 91% (Abuaf et al, 1999;Kvedariene et al, 2006;Laxenaire et al, 1999;Monneret et al, 2002;Moss, 1995;Stellato et al, 1991). This sensitivity is lower (36%) when the marker CD203c is used (Sudheer et al, 2005). However, results are discordant; Kvedarine et al (Kvedariene et al, 2006) observed in 47 patients a sensitivity of 36% and a specificity of 93% performing BAT (CD63 in whole blood).…”
Section: Basophil Activation Test In Muscle Relaxant Allergic Reactionsmentioning
confidence: 62%
“…Relevant studies have found that BAT sensitivity and specificity for muscle relaxants varied from 36% to 92% and 93% to 100%, respectively (Sudheer et al, 2005). Most of these studies reported a high specificity and a sensitivity above 50%, reaching 91% (Abuaf et al, 1999;Kvedariene et al, 2006;Laxenaire et al, 1999;Monneret et al, 2002;Moss, 1995;Stellato et al, 1991).…”
Section: Basophil Activation Test In Muscle Relaxant Allergic Reactionsmentioning
confidence: 99%
“…Accordingly, a difference between sensitivity of both test has been previously reported in the diagnosis of allergy. Authors comparing basophil activation tests, using either CD63 and CD203c in diagnosis of latex allergy, insect venom allergy, drug allergy and found that sensitivity of CD203c was considerably higher than CD63 for the diagnosis of latex allergy [22] and insect venom allergy [23], whereas in diagnosis of allergy to muscle relaxants Sudheer et al [24] found better sensitivity of CD63 assay (79%) in comparison with CD203c assay (36%).…”
Section: Discussionmentioning
confidence: 99%
“…The basophil activation assay has previously been used to diagnose drug allergy, particularly for sensitivity to beta-lactams, where test sensitivity approaches 50% [10]. For allergy to non-steroidal anti-inflammatory agents, the BAT has been shown to have a sensitivity of 63% and a specificity of 93% [13] and for anaesthetic allergy due to neuromuscular blocking drugs the sensitivity of the BAT is 79% [14]. The high sensitivity and specificity of this test in our study supports its potential role in the investigation of allergy to Gelofusine.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 3 Summary of CD63 expression on basophils incubated with Gelofusine diluted 1 : 5 (solid bar) or 1 : 2 (white bar ) in stimulation buffer and neat (grey bar) for patients sensitive to Gelofusine (1-6), healthy controls (7-9) and control patients allergic to neuromuscular blocking drugs (10)(11)(12)(13)(14). The dotted line shows the cut-off of 3.6% as determined by a receiver operating characteristic curve analysis.…”
Section: E Apostolou Et Al Ae Anaphylaxis To Gelofusinementioning
confidence: 99%